Oral Manifestations of Hyperparathyroidism and Its Management-A Review - R.Hariharan1 , N.Anitha2 , L.Malathi2 , N. Aravindha Babu3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Endocrine system is the important system of human body responsible for maintaining the homeostasis andsome other physiological functions by releasing hormones from the endocrine gland. Parathyroid glandis one of the important endocrine glandproducing parathyroid hormone. Parathyroid hormone plays animportant role in maintaining the calcium and phosphorous metabolism and has a direct influence overthe mineralization of bone and teeth. Disorders in parathyroid gland such as hyperparathyroidism andhypoparathyroidism causes altered levels of secretion of parathormone which may cause various symptomsincluding the oralmanifestations such as brown tumor, loss of bone density, increased caries occurrencerate, high risk of bone fracture etc. The aim of this article is to creating the awareness among the dentalprofessionals about the risk and preventive measures in treating the patients with hyperparathyroidism.